Natural products modulate NLRP3 in ulcerative colitis - Xue, Jia-Chen; Yuan, Shuo; Hou, Xiao-Ting; Meng, Huan; Liu, Bao-Hong; Cheng, Wen-Wen; Zhao, Ming; Li, Hong-Ben; Guo, Xue-Fen; Di, Chang; Li, Min-Jie; Zhang, Qing-Gao (Frontiers in Pharmacology, 2023)
Ulcerative colitis (UC) is a clinically common, progressive, devastating, chronic inflammatory disease of the intestine that is recurrent and difficult to treat. Nod-like receptor protein 3 (NLRP3) is a protein complex composed of multiple proteins whose formation activates cysteine aspartate protease-1 (caspase-1) to induce the maturation and secretion of inflammatory mediators such as interleukin (IL)-1β and IL-18, promoting the development of inflammatory responses. Recent studies have shown that NLRP3 is associated with UC susceptibility, and that it maintains a stable intestinal environment by responding to a wide range of pathogenic microorganisms. The mainstay of treatment for UC is to control inflammation and relieve symptoms. Despite a certain curative effect, there are problems such as easy recurrence after drug withdrawal and many side effects associated with long-term medication. NLRP3 serves as a core link in the inflammatory response. If the relationship between NLRP3 and gut microbes and inflammation-associated factors can be analyzed concerning its related inflammatory signaling pathways, its expression status as well as specific mechanism in the course of IBD can be elucidated and further considered for clinical diagnosis and treatment of IBD, it is expected that the development of lead compounds targeting the NLRP3 inflammasome can be developed for the treatment of IBD. Research into the prevention and treatment of UC, which has become a hotbed of research in recent years, has shown that natural products are rich in therapeutic means, and multi-targets, with fewer adverse effects. Natural products have shown promise in treating UC in numerous basic and clinical trials over the past few years. This paper describes the regulatory role of the NLRP3 inflammasome in UC and the mechanism of recent natural products targeting NLRP3 against UC, which provides a reference for the clinical treatment of this disease.